Orthodontic Study Model Discrepancy Analysis on Mixed Dentition: A Narrative Review - Triwardhani, Ari; Putranto, Ananda Firman; Utami, Raihan Nadia (Indonesian Journal of Dental Medicine, 2022)
Background: Attention in the form of dental treatment should be given to the phase of children's teeth that are still in the growth and development stage. The analysis of mixed dentition phase arch is an important criterion in determining the orthodontic treatment plan. Ideally, there is sufficient space so that unerupted teeth can erupt into the oral cavity and not cause crowding of teeth. Several analyzes are needed to confirm the orthodontic diagnosis, one of which is the analysis of the study model. The most widely used alternating mixed dentition analysis is the analysis of the Moyers prediction table and the analysis of the Tanaka-Johnston equation. Both analyzes came from populations of Northern European ancestry but proved unapplicable to populations of various races. Purpose: The purpose of this study aims to determine whether the analysis of the Moyers prediction table and the analysis of the Tanaka-Johnston equation is an accurate analysis if used in several populations through narrative review. Review: Based on the results of the research that has been done, certain populations showed higher prediction results than the actual value. Conclusion: The analysis of the Moyers prediction table and the Tanaka-Johnston equation is not suitable if applied to certain populations, because the results differ from the actual value with the predicted value.